ANALISIS TOKSIKOLOGI BAHAN KIMIA OBAT DALAM JAMU TRADISIONAL: PENDEKATAN MELALUI KROMATOGRAFI LAPIS TIPIS: Toxicological Analysis of Synthetic Drug Adulterants in Traditional Herbal Medicine: An Approach Using Thin Layer Chromatography - Hilmia Lukman; Vivi Shofia (Politeknik Unggulan Kalimantan, 2026)
Traditional herbal medicines are widely used due to their perceived safety and natural origin; however, illegal addition of pharmaceutical substances such as paracetamol and sodium diclofenac poses adverse health effects. The objective of this study was to determine whether paracetamol and sodium diclofenac were present in jamu pegal linu samples via Thin Layer Chromatography (TLC) analysis. The study obtained all samples from local herbal stores in Pajarakan, Probolinggo. TLC analysis on silica gel GF254 plates was performed with compound-specific solvent systems: a 4:1 (v/v) ethyl acetate-chloroform mixture for paracetamol, and a 3:2 (v/v) ethyl acetate-n-hexane mixture for sodium diclofenac. Results revealed paracetamol was detected in three out of four samples with a retardation factor (Rf) of 0.61, while sodium diclofenac was found in three samples with Rf values around 0.90. One sample showed no presence of both compounds. These findings indicate illegal adulteration of herbal medicine, which may cause liver toxicity, kidney impairment, and cardiovascular risks. Therefore, strict supervision and consumer education are essential to prevent adverse health impacts.